The effect of zirconium on the perovskite phase formation of barium zirconium titanate nanoparticles by the sonochemical method - Wirunchit, Supamas; Baitahe, Rattanai; Vittayakorn, Wanwilai; Vittayakorn, Naratip; Maensiri, Santi (My University, 2016)
The sonochemical technique is a powerful synthetic method for the production of nanostructured inorganic powders. Monosized spherical barium zirconium titanate [Ba(ZrxTi1-x)O3; BZT], with x = 0.00, 0.05, 0.20 and 0.40 nanoparticles, were synthesized successfully through sonochemical reaction. The phase formation as well as crystal structure and morphology were investigated. The as-prepared powders were identified by X-ray diffraction (XRD). The cubic perovskite structure of BZT was formed completely in a short irradiation time without the calcination process. The lattice parameter (a) of the samples increased with increasing zirconium concentration. Furthermore, when the concentration of zirconium increased, the reaction time must be increased in order to obtain phase-pure perovskite. The BZT nanoparticles showed a monosized spherical shape that was different from that in other preparation methods. The morphology of the products was very close to spherical, with the particle size distribution being rather narrow.
Keywords: barium zirconium titanate; nanoparticle; Sonochemical method; ultrasonic irradiation